Adaptation the methods of researching visual arts into audio art - Edmund Feldman’s critical method in the study of an artistic radio work - Kowalska-Elkader, Natalia (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The main aim of this chapter is to describe Feldman's critical method and then to adapt it into artistic radio genres. The four-stage method is described in the first part of the text, and in the second part it is adapted to the radio field in the context of research into sound and radio art, as well as in relation to radio criticism.